PRACTICE OF INFORMED CONSENT FOR THE TREATMENT OF TUBERCULOSIS - sultana Habibullah; Salahuddin Afsar; Tehzeeb Anwar (Journal of the Dow University of Health Sciences, 2008)
Objective: To find out the practice o f inform ed consent obtained and opinion for seeking it, from patients enrolled under direct observation treatm ent short course for the treatm ent o f tuberculosis in three public sector chest clinics o f Karachi and recommendations accordingly. Study design: A cross-sectional hospital based survey. Methodology: This survey was conducted on138 patients selected by systematic random sampling method from Lyari, N azim abad and M alir chest clinics o f Karachi. Independent variables o f this study were age, gender, educational level, socio-econom ic status, place o f residence and habits o f the patients enrolled in direct observation treatm ent short course. D ependent variables o f this study were inform ation about the diagnosis of the disease, drug’s dose, duration, intake method, its side effects and voluntary consent/approval for enrolling in the treatm ent regime prescribed by the health care provider. Inclusion criteria o f this study w ere confirm ed diagnosed case o f tuberculosis according to criteria set by the said clinic, in the initial intensive phase o f the treatment. Exclusion criteria were patients o f tuberculosis given treatm ent on trial basis or patients in the continuation phase o f treatment.